2014
DOI: 10.1002/pros.22891
|View full text |Cite
|
Sign up to set email alerts
|

Experimental autoimmune prostatitis induces microglial activation in the spinal cord

Abstract: Background The pathogenesis of chronic prostatitis/chronic pelvic pain syndrome is unknown and factors including the host’s immune response and the nervous system have been attributed to the development of CP/CPPS. We previously demonstrated that mast cells and chemokines such as CCL2 and CCL3 play an important role in mediating prostatitis. Here, we examined the role of neuroinflammation and microglia in the CNS in the development of chronic pelvic pain. Methods Experimental autoimmune prostatitis (EAP) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 44 publications
2
40
0
4
Order By: Relevance
“…Our study revealed that TRPV1 KO mice with EAP (TRPV1 KO‐EAP) do not show evidence of sensitization or changes in response frequency at any time point compared to naive TRPV1 KO (TRPV1 KO‐Naive) mice (Figure A). In contrast, B6 mice with EAP have an increased response frequency compared to naive cohorts at days 7, 14, and 20 (Figure B) with this response known to be chronic beyond day 20 (an additional 17 days) . The present data suggests that TRPV1 channels play an essential role in the development of pelvic tactile allodynia in our mouse model of CP/CPPS.…”
Section: Resultsmentioning
confidence: 55%
“…Our study revealed that TRPV1 KO mice with EAP (TRPV1 KO‐EAP) do not show evidence of sensitization or changes in response frequency at any time point compared to naive TRPV1 KO (TRPV1 KO‐Naive) mice (Figure A). In contrast, B6 mice with EAP have an increased response frequency compared to naive cohorts at days 7, 14, and 20 (Figure B) with this response known to be chronic beyond day 20 (an additional 17 days) . The present data suggests that TRPV1 channels play an essential role in the development of pelvic tactile allodynia in our mouse model of CP/CPPS.…”
Section: Resultsmentioning
confidence: 55%
“…EAP induced chronic pelvic pain, which is consistent with many other studies. Many proinflammatory cytokines in the prostate are associated with peripheral and central neuronal signaling, resulting in pelvic pain . We found for the first time that HCP too leads to chronic pelvic pain.…”
Section: Discussionmentioning
confidence: 67%
“…Many proinflammatory cytokines in the prostate are associated with peripheral and central neuronal signaling, resulting in pelvic pain. 10,21 We found for the first time that HCP too leads to chronic pelvic pain. We do not yet know the mechanisms of induction of chronic pelvic pain in the HCP model, but we previously observed inflammation and fibrosis accompanied by a significant increase in the protein levels of TNF-α, IL-6, and IL-8 in the inflamed prostate.…”
Section: Discussionmentioning
confidence: 82%
“…Among the different chemokines able to activate CCR1 [15], CCL3 (MIP-1a, macrophage inflammatory protein-1a) and CCL5 (RANTES, reduced upon activation normal T-cell expressed and secreted) are particularly related to nociception. CCL3 mRNA is up-regulated in the spinal cord of inflamed rats [16] and the spinal expression of CCL3 increases in mice with prostatitis [17] or nerve injury [11] being its neutralization with a specific antibody able to evoke analgesic effects [12]. CCL5 has been also previously related to hypernociceptive reactions associated with neuropathic injury [18] and tumour development [10,19,20].…”
mentioning
confidence: 98%